Cleaning Reduces Mycotoxin Contamination in Corn - A. Yoder; M. D. Tokach; J. M. DeRouchey; C. B. Paulk; C. R. Stark; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2017)
A single load of corn naturally contaminated with aflatoxin (1,074 ppb), fumonisin (8.3 ppm), and ochratoxin A (206 ppb) was procured from central Oklahoma to evaluate the role of cleaning to remove mycotoxin contamination in corn. Corn was divided into twenty 333-lb lots, which were then cleaned using an EBM Gentle Roll corn cleaner to remove overs (material>1/2 inches) and unders (material<3/16 inches). The resultant 4 treatments included: 1) uncleaned corn; 2) overs from cleaned corn; 3) cleaned corn; and 4) unders from cleaned corn. Samples of each fraction were analyzed for mycotoxin content using multiclass liquid chromatography tandem mass spectrometry. Cleaning generated approximately 6% screenings (unders + overs), and reduced (P<0.05) aflatoxin by an average of 26%. Cleaning also reduced (P<0.05) fumonisin by 45%, but did not impact ochratoxin A. Unders had nearly 4 times the aflatoxin and 7.5 times the fumonisin as the uncleaned corn. In conclusion, cleaning corn may substantially reduce mycotoxin contamination, but the resultant screenings should be used cautiously.
Keywords: corn; feed; mycotoxin; screenings